A review of magnetic nanocomposites for EMI shielding: synthesis, properties, and mechanisms - Ismail, Ismayadi; Azis, Raba’ah Syahidah (Springer, 2024)
With the proliferation of electronics and wireless devices, managing disruptive electromagnetic interference (EMI) has become imperative. This review examines recent advancements in magnetic nanocomposite materials for EMI shielding applications. Fundamentally, these multifunctional nanocomposites leverage the synergy between magnetic and conductive components to facilitate exceptional microwave absorption and reflection capabilities. The analysis begins by elucidating the physics of EMI shielding mechanisms, including reflection, absorption, and multiple internal reflections. Building on electromagnetic principles, the magnetic properties of nanocomposite constituents are discussed, emphasizing their role in enabling magnetic loss, dielectric loss, and eddy current induction within materials. The review then extensively explores common synthesis techniques for magnetic nanocomposites, such as co-precipitation, sol–gel, and hydrothermal methods. A detailed examination of the resulting nanocomposite characteristics and EMI shielding performance provides useful insights into composition-structure–property relationships. Moreover, innovative fabrication strategies based on physical vapor deposition are highlighted for their precision in controlling nanostructure morphology. Subsequently, the review dives into the nuanced interplay between dielectric, conductive, and magnetic nanocomposite components and their synergistic influence on EMI shielding. Current challenges are also discussed, encompassing issues like nanoparticle agglomeration and environmental durability. Finally, scalable production methods are reviewed as a crucial step towards real-world applications. This all-encompassing review synthesizes the frontiers of magnetic nanocomposite engineering, design, and fabrication for next-generation EMI shielding materials with tailored, application-specific shielding capabilities.